Agent-Based Automatic Shore Operating Scheduling for a Container Terminal - Nannan Yan; Yuan Zhou (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This  paper  established  berth  allocation  and  quay crane  scheduling  models  of  shore  operating  for  a  container terminal. Furthermore, the structure of the berth - quay crane scheduling   agent   is   also   given.  Finally,   an   example   using genetic  algorithm  to  resolve  the  berth  allocation  model  and agent  technology  is  shown. The  experiment result shows that the  use  of  intelligent theory  and  technology  can  provide  an effective way for  container terminal operating scheduling. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1989